STUDIES ON THE AGE AND GROWTH OF THE MALABAR SOLE, CYNOGLQSSUS SEMIFASCIATUS, DAY - Seshappa, G; Bhimachar, B S (Indian Journal of Fisheries, 2016)
FOR the development of a scientific management policy for any fishery, itis essential to know among other things, the rate of growth of the speciesconcerned and the changes in the age-composition of its stocks from seasonto season and from year to year. The present paper deals with the resultsof investigations which were designed to collect information on these twoaspects in relation to the Malabar sole, Cynoglossus semifasciatus. Althoughthis forms a valuable fishery along the Malabar Coast no attention has beenpaid in the past to a detailed investigation of its biology